Force systems yielded by different designs of T-loop - Thiesen Guilherme; do Rego Marcus Vinicius Neiva Nunes; de Menezes Luciane Macedo; Shimizu Roberto Hideo (Australasian Orthodontic Journal, 2005)
Objectives: To determine the mechanical characteristics of beta-titanium T-loops with and without helices, with 0 and 180 degree gable bends and constructed from 0.017 inch x 0.025 inch and 0.019 inch x 0.025 inch wire.